Evaluasi Penggunaan Antibiotik Pada Pasien Infeksi Saluran Kemih Rawat Inap Di RSUD Kabupaten Sukoharjo Tahun 2014 - Sutarman, Reza Hashemi; , Dra. Nurul Mutmainah, M.Si., Apt (2016)
Urinary Tract Infection (UTI) is a condition that happens due to bacterial invasion in the urinary tract. Urinary tract infections are caused by Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa. The suggested treatment of urinary tract infection is antibiotic therapy. The use of antibiotics will cause various problems such as lack of effective treatments, high risks to patient safety, bacterial resistance to antibiotics and high cost treatment. The purpose of this study is to describe the use of antibiotics for urinary tract infections (UTI) hospitalized patients and determine the appropriateness antibiotics use for the patients with urinary tract infection (UTI) hospitalized at X Regional Hospital Sukoharjo in 2014 in terms of the following aspects; the right indication, the right medicine, the right patient and the right dosage. This study is considered as retrospective observational (non-experimental) research and the data was analyzed by using descriptive methods. The sampling was obtained by using purposive sampling technique based on the writer criteria. Based on the results of the study, it can be concluded that a single type of antibiotics used are ceftriaxone (35.78%), cefotaxime (17.89%), ciprofloxacin (12.63%), and amoxicillin (29.47%). The uses of combination type of antibiotic used are ceftriaxone and cefotaxime (4.23%). Based on the results of this study, the use of drug that meet the criteria of proper indications is 100%, the right drug is 96.84%, the right patient is 100%, and the right doses is 6.24%.